Community-Based Participatory Research in Education: Empowering Women School Leaders in KwaZulu-Natal - Ntombikayise Nkosi; Mncedisi Christian Maphalala (E-Journal of Humanities, Arts and Social Sciences, 2025)
Community-based participatory research (CBPR) has emerged as a robust methodology to foster collaboration and empowerment in educational contexts. This paper explores the application of CBPR in the context of education, focusing specifically on its role in empowering women school leaders in KwaZulu-Natal, South Africa. Through a qualitative research approach, this study was conducted in close collaboration with women school leaders and with community stakeholders and schools’ active and integral participation. The findings of this study underscore the importance of community-based participatory approaches in empowering women school leaders and advancing gender equity in educational leadership in KwaZulu-Natal. The key findings highlight the following themes: gendered power dynamics in educational leadership, the impact of CBPR on women’s empowerment, identification of empowerment strategies, collective action and community support, and the potential for transformative change. These findings provide valuable insights for policymakers, educators, and community stakeholders, serving as a guide for promoting inclusive and equitable educational practices.